1989
DOI: 10.1159/000215893
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Effects of Three Thrombin Inhibitors in a Rat Model of Laser-Induced Thrombosis

Abstract: The antithrombotic effects of three thrombin inhibitors (hirudin, NAPAP and argidipine) were investigated in an experimental thrombosis model using laser lesions of rat mesenteric venules. Furthermore, their in vitro anticoagulant activity (partial thromboplastin time, thrombin time, Heptest, inhibition of factor Xa and factor Xa) in human platelet poor plasma (PPP) and their in vitro and ex vivo activities were studied in rat plasma. All three thrombin inhibitors showed significant and dose-dependent antithro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
2
10
1
Order By: Relevance
“…On the other hand, there was a positive correlation between the anticoagulant effect of r-hirudin (HBW 023) and its plasma level after both intravenous and subcutaneous injection in rhesus mon keys [22], Taken together, these data suggest that the effects of r-hirudin on coagulation and bleeding measurements correlate with plasma level but that inhibition of thrombo sis, at least under certain conditions, lasts longer. A similar longer-lasting antithrom botic effect of natural hirudin and of two other thrombin inhibitors compared to their anticoagulant activity has been described by Krupinski et al [23], In this context the investigations by Friedberg et al [24] are interesting: they demonstrated that hirudin markedly accelerated the displacement of bound factor Xa from cultured bovine aortic endothelium. This may suggest a novel mechanism of anticoagulation.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, there was a positive correlation between the anticoagulant effect of r-hirudin (HBW 023) and its plasma level after both intravenous and subcutaneous injection in rhesus mon keys [22], Taken together, these data suggest that the effects of r-hirudin on coagulation and bleeding measurements correlate with plasma level but that inhibition of thrombo sis, at least under certain conditions, lasts longer. A similar longer-lasting antithrom botic effect of natural hirudin and of two other thrombin inhibitors compared to their anticoagulant activity has been described by Krupinski et al [23], In this context the investigations by Friedberg et al [24] are interesting: they demonstrated that hirudin markedly accelerated the displacement of bound factor Xa from cultured bovine aortic endothelium. This may suggest a novel mechanism of anticoagulation.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, Krupinski et al [8] studied rat mesenteric vessels using an argon laser model and reported that the antithrombotic effect of argatroban (0.5 mg/kg) lasted as long as 4 h. It seems likely that the differences between the present results and those of Krupinski et al [8] were due to the nature of the blood vessels and the type of laser used for the induction of thrombosis. Many properties of cerebral ves sels are known to be different from those of other vessels [ 1 -5], and studies by others have shown that thrombi generated with an argon laser are readily disrupted by flowing blood.…”
Section: Discussioncontrasting
confidence: 87%
“…The different proper ties of cerebral vessel walls from those of other blood vessels have been emphasized, for example the existence of a blood-brain bar rier, the appearances of intercellular junctions and the variable enzyme activities of endothe lial cells [1][2][3]. In addition, it has been re ported that thrombomodulin is absent from cerebral vessels [4,5], although this finding has been disputed [6], Models of thrombosis have been used for the assessment of the anti thrombotic effect of antiplatelet or anticoagu lating agents in several experimental animals using lasers and mesenteric blood vessels [7][8][9][10][11][12][13]. It is important to evaluate the effects of these agents on cerebral vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The effective energy below the objective X 50 was adjusted to 0.12 W. The exposure times of the laser beam were 1/15 s. An intestinal loop exposed through a hypogastric incision and continuously irrigated with prewarmed (37 °C) saline was spread on a self-constructed device mounted on the microscope table. The laser beam was directed at small mesenteric venules (diameter 25-30 pm) in the fat-free portion of the mesentery [5][6][7]. Thrombus formation was evaluated by direct obser vation through the microscope.…”
Section: Methodsmentioning
confidence: 99%